Glasgow coma scale compared to other trauma scores in discriminating in-hospital mortality of traumatic brain injury patients admitted to urban Indian hospitals: A multicentre prospective cohort study. Issue 1 (January 2023) - Basak, Debojit; Chatterjee, Shamita; Attergrim, Jonatan; Sharma, Mohan Raj; Soni, Kapil Dev; Verma, Sukriti; GerdinWärnberg, Martin; Roy, Nobhojit
Highlights: GCS is one of the most commonly used trauma scores and is a good predictor of outcome in TBI patients. There are other more complex scores like RTS, MGAP, GAP, KTS with additional physiological parameters to GCS. This study compares discrimination of GCS to that of the above complex trauma scores for 24-hour and 30-day in-hospital mortality in adult TBI patients, in a resource limited LMIC setting. This study indicates that discrimination of GCS is comparable to that of more complex trauma scores in predicting 24-hour and 30-day mortality of adult TBI patients in resource limited LMIC settings. Abstract: Background: Glasgow Coma Scale (GCS ) is one of the most commonly used trauma scores and is a good predictor of outcome in traumatic brain injury (TBI ) patients. There are other more complex scores with additional physiological parameters. Whether they discriminate better than GCS in predicting mortality in TBI patients is debatable. The aim of this study was to compare the discrimination of GCS with that of MGAP, GAP, RTS and KTS for 24-hour and 30-day in-hospital mortality in adult TBI patients, in a resource limited LMIC setting. Method: We analysed data from the multicentre, observational trauma cohort Towards Improved Trauma Care Outcome (TITCO) in India. We included all patients 18 years or older, admitted from the emergency department with TBI. The Area Under the Receiver Operating Characteristic (AUROC) curve was used to quantify and compare the discrimination of all scores: GCS; Revised Trauma Score (RTS ); mechanism, GCS, age, systolic blood pressure (MGAP ); GCS, age, systolic blood pressure (GAP ) and Kampala Trauma Score (KTS ) in the prediction of 24-hour and 30-day in-hospital mortality. Results: A total of 3306 TBI patients were included in this study. The majority were within the GCS range 3-8. The commonest mechanism of injury was road traffic injuries [1907(58.0%)]. In-hospital mortality was 27.2% (899). There was no significant difference in discrimination in 24-hour in-hospital mortality when comparing GCS with MGAP and GAP. While GCS performed better than KTS, RTS performed better than GCS. For 30-day in-hospital mortality, GCS discriminated significantly better compared with KTS, but there was no significant difference when compared to MGAP and RTS. GAP discriminated significantly better when compared with GCS. Conclusion: This study shows that the discrimination of GCS is comparable to that of more complex trauma scores in predicting 24-hour and 30-day in-hospital mortality in adult TBI patients in a resource limited LMIC setting.